Who Failed to Go Public with Best Efforts Offerings - Sung-Il Cho (Journal of Small Business Finance, 1993)
This paper presents evidence on the failed initial public offerings that used best efforts contracts. Out of 732 best efforts IPOs attempted in 1980-84, 186 IPOs (about one fourth) failed to meet minimum sales requirement and were subsequently withdrawn. Offerings with greater uncertainty about their true value failed more frequently. The failure rate was not significantly different between “all or none” type offerings and “minimum and maximum” type offerings. Regional investment bankers managed the most of best efforts IPOs and the average underpricing of their offerings was smaller than that of offerings managed by submajor bracket investment bankers. It is noteworthy that bankers with a record of failed offerings did not seem to lose their future business and relatively small issuing firms continued to rely on these bankers to go public.
Keywords: G32; G12; 650; IPO; Initial Public Offering; Best Efforts